The Interdisciplinary Approaches in Climate Change-Based Education: Bibliometric Analysis and Literature Review - Aldi Alfiansyah Wibowo; Paidi Paidi; Kintan Limiansi (Department of Biology Education Faculty of Teacher Training and Education Sebelas Maret Un, 2026)
An interdisciplinary approach to climate change-based education is a growing field, but previous research has been limited in mapping trends, gaps, and directions for comprehensive research development. Therefore, this study aims to visualize research trends of interdisciplinary approaches in climate change-based education during the period 2020–2025, identify research gaps, and explore potential innovations and development strategies. This study uses a bibliometric approach and a systematic literature review, drawing on data from the Scopus database. A total of 609 articles were identified at the initial stage of the search, then selected and filtered, leaving 130 that met the criteria for analysis. Data analysis was conducted using VOSviewer and Microsoft Excel 2021. The analysis shows a significant increase in publications over the last six years, with six main keyword clusters. The dominant keywords include “interdisciplinary in education”, “climate change-based education”, and “climate change”. In addition, temporal analysis reveals that topics such as education for sustainable development, strategic approaches, case studies, and prevention and control are emerging themes that have high potential for further research. This research provides a comprehensive mapping of research trends and directions, as well as identifies areas that are still underexplored, serving as a basis for the development of more effective interdisciplinary learning strategies in climate change-based education in the future.